An approach of clinical pharmacist pertaining to solve drug related problems in pediatric patients - Suwitha, S.; Fardan, Mohammed; Shaji, Aswathy M.; Joe, Jimmer; Hasif, K.; Priya, A.; Yadav, K. Arun Chander (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objectives of the study were to assess the outcomes of clinical pharmacist intervention in solving drug related problems in pediatric patients and to identify the drug related problems in accordance with the causes observed. Methods: It was a prospective observational study done over a period of six months (October 2019 to March 2020) at Apollo children’s hospital in Chennai. Results: Total of 480 subjects were enrolled into the study, out of which 248 were male children and 232 were female children. The patients were divided into 4 age groups. In this study 60.41% pediatric patients were prescribed with less than 5 drugs 290 (60.41%). Drug related problems which were identified during the study was classified according to Pharmaceutical Care Network Europe (PCNE) and drug-related problem (DRP) classification (v9.00). The most frequent DRP was drug choice problem 37 (33.33%). The total number of caused drug related problems was 73 and same number of interventions was given by clinical pharmacist. The most frequent cause of drug related problems was identified as dose selection 31 (42.46%). Outcomes of interventions revealed that 70 (95.89%) problems were solved overall. Conclusions: In this study, clinical pharmacist’s level of involvement has shown interesting results. Moreover, they play an essential role in improving patient safety and outcome, reducing cost and providing quality of care for ill patients.